Kontrafakcija XIX a. pirmosios pusės lietuviškų knygų leidyboje - Navickienė, Aušra (Knygotyra, 2005)
Contrafactions or the publications with falsified imprint are not characteristic for the first half of the 19th century in Lithuania. Only one possible case of a contrafaction from the period 1795-1864 is mentioned in the first volume of Lithuanian retrospective bibliography of Lithuanian books (Lietuvos TSR bibliografija. Serija A Knygos lietuvių kalba). These are the repeated editions of the publication About Teetotalers’ Brotherhood (Apej brostwą blaiwistes) by Bishop Motiejus Valančius. They appeared in 1860 and 1861 and could have been printed not in Klaipėda as the title page indicates, but in the Vilnius printing house of J. Zawadzkis. There is no one final opinion about this fact, and the article returns to the publishing history of the book by Valančius because it is important for establishing the beginning of the book relations between Great Lithuania and Lithuania Minor. Usually, it is linked to the publishing of the above-mentioned book in Klaipėda. We agree with the arguments produced by Kazimieras Gečys and dispute other opinions by proving that About Teetotalers’ Brotherhood (Apej brostwą blaiwistes) was published in 1860 and 1861 in the Vilnius enterprise owned by J. Zawadzkis, not in Klaipėda’s E. Vaikinas company. The new arguments are based on the archival material of J. Zawadzkis’ enterprise, published correspondence of book workers, investigation de visu of the remaining copies of the publication, and the analysis of types. The article concludes that there is definite proof that the publications of 1860 and 1861 are contrafactions of the first half of the 19th century. They appeared under conditions and factors that demonstrate opposition to the censorship rules. This opposition served as a model that influenced the behavior of book workers after 1864 and was used from the beginning of the ban on Lithuanian press. If About Teetotalers’ Brotherhood (Apej brostwą blaiwistes) repeated editions appeared in Vilnius, then the beginning of book relations between Great Lithuania and Lithuania Minor has to be moved to the later date after the year 1864, when the first contrafacted publications were published in Lithuania Minor for the inhabitants of Great Lithuania.